2015
DOI: 10.1016/j.chroma.2015.07.121
|View full text |Cite
|
Sign up to set email alerts
|

A one-step preparation method of monolithic enzyme reactor for highly efficient sample preparation coupled to mass spectrometry-based proteomics studies

Abstract: Mass spectrometry (MS) coupled to sample preparation and separation techniques has become a primary tool for proteomics studies. However, due to sample complexity, it is often challenging to achieve fast and efficient sample preparation prior to MS analysis. In recent decades, monolithic materials have been developed not only as chromatographic media, but also as efficient solid supports for immobilizing multiple types of affinity reagents. Herein, the N-acryloxysuccinimide-co-acrylamide-co-N,N'-methylenebisac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The IMER had 200 positive values where it produced higher coverage and there was one instance where the coverage was identical resulting in a value of zero. The IMER digestion presented in this study was faster than previous reports for on-line yeast cell lysate digestion [21, 46, 47] and identified approximately the same number of yeast proteins (541 reported in Feng, et al [21] compared to 507 found in this study). It is important to note that the sample used in this study was the insoluble portion of a yeast cell lysate, containing approximately 60% proteins that are identified as membrane-associated.…”
Section: Resultssupporting
confidence: 55%
“…The IMER had 200 positive values where it produced higher coverage and there was one instance where the coverage was identical resulting in a value of zero. The IMER digestion presented in this study was faster than previous reports for on-line yeast cell lysate digestion [21, 46, 47] and identified approximately the same number of yeast proteins (541 reported in Feng, et al [21] compared to 507 found in this study). It is important to note that the sample used in this study was the insoluble portion of a yeast cell lysate, containing approximately 60% proteins that are identified as membrane-associated.…”
Section: Resultssupporting
confidence: 55%
“…On‐line sample trypsinization can be performed in seconds using an IMER microreactor . Additional, increase of efficacy can be achieved by co‐immobilization with Lys‐C . With a new monolithic bioreactor with 3D‐printed interface stationary phase, high concentration of protease activity can be achieved .…”
Section: Monoliths In High‐throughput Mass Spectrometry‐based Proteomicsmentioning
confidence: 99%
“…Moreover, the advantages of methacrylate‐based monolithic matrices include mechanical and chemical stability, as well as the possibility of synthesis of these materials in various geometrical formats, namely, in the shape of disks, columns or tubes . Owing to the mentioned advantages of monoliths, they have become popular not only for application in different kinds of chromatography and solid‐phase extraction , but also for the preparation of flow‐through immobilized enzyme reactors (IMERs) suitable for proteomics , microfluidic analysis , pharmaceutics , biodiesel and oligosaccharides production, etc. In most cases, the covalent binding of enzyme to the surface of macroporous monoliths was applied .…”
Section: Introductionmentioning
confidence: 99%